Redoing the Demos - Jennings, Bruce (The Hastings Center report, 2021)
Forces including extreme economic inequality, cultural polarization, and the monetizing and privatizing of persons as commodities are undermining the forms of moral recognition and mutuality upon which democratic practices and institutions depend. These underlying factors, together with more direct modes of political corruption, manipulation, and authoritarian nationalism, are undoing Western democracies. This essay identifies and explores some vital underpinnings of democratic citizenship and civic learning that remain open to revitalization and repair. Building care structures and practices from the ground up and developing inclusive and egalitarian modes of solidarity in a pluralistic society are the focus of discussion. The essay argues that solidarity and care are essential relationships and practices of moral recognition upon which democratic political agency and freedom rest. The social-relational lifeworld and the democratic lifeworld are interdependent. Democratic citizenship is itself a relational practice that supports other practices. Democratic governance properly carried out fosters an underlying social solidarity and care and in turn draws moral and political legitimacy upward from them.